2006
DOI: 10.1007/s11434-006-1115-3
|View full text |Cite
|
Sign up to set email alerts
|

Branched alkanes with quaternary carbon atoms in Chinese soils: Potential environmental implications

Abstract: Lipids extracted from 26 modern soils collected from different climate zones in China and Mongolia are analyzed using gas chromatographymass spectrometry. These extracts contain pseudohomologous families of 5,5-diethylalkanes (5,5-DEAs), 6,6-diethylalkanes, 5-butyl-5-ethylalkanes and 6-butyl-6-ethylalkanes, which are first detected in modern soils. All these pseudohomologous series display exclusively odd or exclusively even carbon numbers, clearly indicating a biosynthetic origin, and their carbon number dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
1
12
1
Order By: Relevance
“…Both n-alkylcyclopentanes and n-alkylcyclohexanes ranged from C 16 to C 24 with C max at C 18 -C 20 . A similar distribution of BAQCs, alkylcyclopentanes and alkylcyclohexanes has been reported in soils, ancient sediments, sedimentary rocks, and Antarctic cyanobacterial mats (Kenig et al, 2003(Kenig et al, , 2005Bai et al, 2006;Jungblut et al, 2009). However, recent investigations reporting the presence of these compounds in the extracts of polyethylene bags suggest that they are most probably derived from contamination (Grosjean and Logan, 2007;Brocks et al, 2008).…”
Section: Non-polar Solvent-extractable Compoundssupporting
confidence: 76%
“…Both n-alkylcyclopentanes and n-alkylcyclohexanes ranged from C 16 to C 24 with C max at C 18 -C 20 . A similar distribution of BAQCs, alkylcyclopentanes and alkylcyclohexanes has been reported in soils, ancient sediments, sedimentary rocks, and Antarctic cyanobacterial mats (Kenig et al, 2003(Kenig et al, , 2005Bai et al, 2006;Jungblut et al, 2009). However, recent investigations reporting the presence of these compounds in the extracts of polyethylene bags suggest that they are most probably derived from contamination (Grosjean and Logan, 2007;Brocks et al, 2008).…”
Section: Non-polar Solvent-extractable Compoundssupporting
confidence: 76%
“…The n -alkane distributions demonstrate that all of the woody vegetation (shrubs) maximizes at C 27 and most of the herbaceous vegetation maximizes at C 31 or C 33 (Liu and Huang, 2005; Zhong et al, 2009; Liu and Liu, 2015). Moreover, n -alkanes from modern topsoil with herbaceous vegetation maximize at C 31 in the western Loess Plateau (Wang et al, 2003; Zhong et al, 2009), whereas n -alkanes from modern topsoil with woody vegetation (shrubs) maximize at C 27 or C 29 in the arid region of northwestern China (Bai et al, 2006a, 2006b). Therefore, we interpreted the n -alkane C max as a proxy of vegetation in the Alashan Desert, with the n -alkanes C 27 or C 29 indicating woody vegetation and the n -alkanes C 31 or C 33 indicating herbaceous vegetation.…”
Section: Discussionmentioning
confidence: 99%
“…2,2-dimethyl-, 5,5-diethyl and 3,3,x3,x3-tetraethylalkanes. Based on their apparent occurrence in specific environments, BAQCs were construed as biomarkers for non-photosynthetic, sulfide oxidizing prokaryotes that predominantly inhabit benthic redox boundaries (Kenig et al, 2003) or identified as new proxies indicating variations in soil ecosystems and climates (Bai et al, 2006). However, a biogenic source of BAQCs can be excluded for several reasons.…”
Section: Introductionmentioning
confidence: 99%